Chemical composition of essential oil from Tagetes elliptica Smith “chincho” and antioxidant, antibacterial and antifungal activities - Segovia B., Ingrid K. (2010)
The present research was aimed to determine qualitatively the chemical constituents and antibacterial, antifungal and antioxidant activity of essential oil from leaves of Tagetes elliptica Smith “chincho”, native of the province of Huaraz, Ancash region, which was obtained by the method of distillation with water vapor. Later physicochemical constants were determined, and then made the determination of chemical composition by Gas Chromatography / Mass Spectrometry (GC/MS). By the methods of agar diffusion and agar dilution were determined antimicrobial activities and minimum inhibitory concentration (MIC), respectively, against the following microorganisms: S. aureus ATCC 25933, S. epidermidis (clinical isolate), B. subtilis (environmental strain), E. coli (clinical isolate), P. aeruginosa ATCC 27853, Klebsiella (clinical isolate) and C. albicans ATCC 10231. In tests, the essential oil evidenced antibacterial activity against five strains, being resistant Klebsiella because it showed an inhibition zone <18 mm; against Candida albicans ATCC 10231, showed significant antifungal activity. The MIC against S. aureus, E. coli, P. aeruginosa was 7,62 x 10-1 μg/mL and S. epidermidis, 97,5 μg/mL; to B. subtilis 390 μg/mL and C. albicans 780 μg/mL. With regard to antioxidant activity, there were two tests known as free radical scavenging: Capturing the difenilpicrilhidrazil radical (DPPH) and superoxide radical uptake produced by pyrogallol, with the following results: IC50 = 97,5 μg/mL and IC 50 = 47,5 μg/mL; respectively, which were not significant, taking into account patterns of Trolox and Vitamin C, respectively.